Meritocracy and its discontents : anxiety and the national college entrance exam in China - Howlett, Zachary M., 1976- (Cornell University Press, 2021)
"An ethnography of the National College Entrance Examination, the Gaokao, in contemporary China. Discusses the exam as a fateful rite of passage that justifies and reinforces social inequality and the myth of meritocracy while enabling people to personify the cultural virtues of diligence, grit, composure, and divine favor or luck"--